Exploiting equilibrium-kinetic synergetic effect for separation of ethylene and ethane in a microporous metal-organic framework - Ding, Qi (Sci Adv, 2020)
Physisorption is a promising technology to cut cost for separating ethylene (C(2)H(4)) from ethane (C(2)H(6)), the most energy-intensive separation process in the petrochemical industry. However, traditional thermodynamically selective adsorbents exhibit limited C(2)H(4)/C(2)H(6) selectivity due to their similar physiochemical properties, and the performance enhancement is typically at the expense of elevated adsorption heat. Here, we report highly-efficient C(2)H(4)/C(2)H(6) adsorption separation in a phosphate-anion pillared metal-organic framework ZnAtzPO(4) exploiting the equilibrium-kinetic synergetic effect. The periodically expanded and contracted aperture decorated with electronegative groups within ZnAtzPO(4) enables effective trapping of C(2)H(4) and impedes the diffusion of C(2)H(6), offering an extraordinary equilibrium-kinetic combined selectivity of 32.4. The adsorption heat of C(2)H(4) on ZnAtzPO(4) (17.3 to 30.0 kJ mol(−1)) is substantially lower than many thermodynamically selective adsorbents because its separation capability only partially relies on thermodynamics. The separation mechanism was explored by computational simulations, and breakthrough experiments confirmed the excellent C(2)H(4)/C(2)H(6) separation performance of ZnAtzPO(4).